EFEKTIVITAS KEGIATAN EMPLOYEE RELATIONS BANDAR DJAKARTA ALAM SUTERA DALAM MENINGKATKAN MOTIVASI KERJA KARYAWAN - Zahra Dias Widiyanti; Arya Andhika Weynanda (Indonesian Journal of Digital Public Relations (IJDPR), 2023)
This research examines the effectiveness of employee relations conducted by Bandar Djakarta Alam Sutera in increasing employee motivation. This research uses a descriptive qualitative method with a case study approach through interviews, observations and document studies. The research subjects were carried out by the Operational Manager, Head of Public Relations, and Head of Service and Bar. The results of the study found that employee relations activities were effective in increasing employee motivation. The phenomenon of this research departs from the condition felt by employees after the Covid-19 pandemic, namely experiencing a decrease in work motivation when they have to adapt again to open spaces. This is indicated by the number of employees who arrive late to the location and the level of quality and speed of service provided. So in this case, a special focus and strategy is needed in the form of employee relations in order to maintain service quality by managing a large number of employees. In this study, the authors explain how the implementation of employee relations activities at Bandar Djakarta Alam Sutera and how effective they are in increasing employee motivation. Implementation of employee relations activities goes according to Rosady Ruslan's description of employee relations, so it is very effective in increasing employee motivation. Keywords: employee relations, work motivation, employee